2016
DOI: 10.5897/ajb2016.15560
|View full text |Cite
|
Sign up to set email alerts
|

Perennial soybean seeds coated with high doses of boron and zinc

Abstract: The objective of this work was to study combinations of high doses of boron (B) and zinc (Zn) in the recoating of perennial soybean seeds, in order to provide these nutrients to the future plants. The physical, physiological and nutritional characteristics of the coated seeds and initial development of plants in a greenhouse were evaluated. Tests carried out in the laboratory were conducted in a completely randomized design, and the experiments completed in a greenhouse were a randomized block design. The coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…These treatments were then poorly effective in coating adhesion. Our results corroborate the findings by Acha, Vieira and Freitas (2016), who observed that coating perennial soybean seeds with zinc (Zn) and B doses impaired seed quality.…”
Section: Resultssupporting
confidence: 92%
“…These treatments were then poorly effective in coating adhesion. Our results corroborate the findings by Acha, Vieira and Freitas (2016), who observed that coating perennial soybean seeds with zinc (Zn) and B doses impaired seed quality.…”
Section: Resultssupporting
confidence: 92%
“…GroundEye ® was efficient in determining the maximum and minimum diameters of coated Stylosanthes sp. and perennial-soybean seeds in the studies of Acha et al (2016), Silva et al (2017), Acha et al (2018) and Xavier and Vieira (2018). These authors obtained significant increases for those variables with the different coating methodologies Table 3.…”
Section: Resultsmentioning
confidence: 84%
“…In the greenhouse, the seeds achieved an ESI of 1.7% and an emergence percentage 26.5% (intact seeds); and an ESI of 4.1% and 51.5% emergence (scarified seeds). In both environmental conditions, chemical scarification showed to be efficient, breaking the integument dormancy specific to seeds of Neonotonia wightii (Acha et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations